FEATURES OF THE DEVELOPMENT OF HIGH-TECH AND HIGH-TECH INDUSTRIES - E. Merzlyakova; V. Sergeeva; N. Makarov (Вестник Северо-Кавказского федерального университета, 2022)
The article deals with the theoretical aspects of the activities of high-tech and high-tech industries. The classification of industrial production by the level of manufacturability is given. The role and importance of high-tech and high-tech industries for the domestic economy, as well as for the formation of the core of a new technological order and Industry 4.0 are outlined. Taking into account the fact that the development of such industries is directly related to the overall level of innovation activity in the country, the main indicators of innovation activity are analyzed. In addition, an assessment of the innovative activities of hightech industries was carried out, in accordance with which the problems and prospects for their development were identiied.